2014
DOI: 10.3382/ps.2013-03478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pretransport handling stress on physiological and behavioral response of ostriches

Abstract: Ostrich (Struthio camelus) production is a relatively young industry and there has been little research on ostrich welfare during pretransport handling and the transportation process. A heavy body with a high center of gravity makes ostriches' handling and transportation problems different from other livestock. The main objective of this study was to investigate the effects of the pretransport holding time duration on ostrich behavior and physiological responses. A second objective was to identify and validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…It also reduced the animals’ live weight gain [26, 27] and the quality of animal products [28, 29], and resulted in significant weight loss in emus [30]. The posttransport body weight of all birds was significantly lower than their pretransport body weight [31]. In our present study, a greater weight loss was presented in the road transport treated chicks, which was in agreement with the previous study.…”
Section: Discussionsupporting
confidence: 90%
“…It also reduced the animals’ live weight gain [26, 27] and the quality of animal products [28, 29], and resulted in significant weight loss in emus [30]. The posttransport body weight of all birds was significantly lower than their pretransport body weight [31]. In our present study, a greater weight loss was presented in the road transport treated chicks, which was in agreement with the previous study.…”
Section: Discussionsupporting
confidence: 90%
“…Posttreatment handling (weighing, transportation, and stunning) was the same for all groups and quails showed similar corticosterone values, possibly for these being unfamiliar activities. When facing stress-causing agents, the birds, activate the breakdown of hepatic glycogen and gluconeogenesis, consequently increasing blood glucose (Yalçin et al, 2004;Bejaei et al, 2014), as seen in this experiment. However, other scientific studies have shown that glucose concentrations remained stable in different periods of broiler feed restriction during growth (De Jong et al, 2003;Rajman et al, 2006) or fasting for several days in Japanese quails (Sartori et al, 1995); therefore, it is suggested that the glycaemic response is different in face of possible acute or chronic stressors.…”
Section: Discussionmentioning
confidence: 67%
“…Stress in birds renders them prone to many undesirable outcomes which result in production losses in poultry (Huchzermeyer, 1997). The environmental stress factors include temperature, humidity, handling, transport, stocking density, noise, poor access to feed, hierarchical dominance, and presence of predators around the farm (Deeming and Bubier, 1999;Shanawany and Dingle, 1999;Bejaei and Cheng, 2014;Navarro et al, 2019). These environmental factors influence the feeding behaviour of ostriches and can lead to development of conditions like pica (Samson, 1996).…”
Section: Nexus Of Behaviour and Stressmentioning
confidence: 99%